The benefits of and challenges faced by worldwide federal governments in implementing the telework program - Kang, Eng Thye; Shek Osman, Wan Rozaini; Othman, Nafishah; Abd Razak, Rafidah; Mat Aji, Zahurin (2012)
Problem statement: In recent decades, the telework program implemented in advanced and developed countries, has started to draw the interests of many parties towards understanding their experiences.The efforts to understand telework benefits and challenges would serve as an important basis prior to considering the adoption any telework program by the federal government agencies.Books, websites and journals were the primary sources that allowed the conduct of intensive literature reviews to obtain a full understanding of the telework issue.In terms of benefits, employers gain the competitive edge; less disruption of operations and better services to remote communities.Employees could enjoy the flexible time schedule; better family dependent care; less commuting costs and time; and higher productivity. Society could enjoy new job creation; less environmental pollution and work redistribution. In contrast, the challenges experienced are insufficient central federal government funding; top management resistance; and the difficulty to measure employee productivity. No program offers 100 percent unlimited benefits.Telework, in this case, is no different.Nevertheless, no one size fits all. Further tailoring of telework policy to suit different government agencies’ specific needs is an important approach to ensure its success.